2007
DOI: 10.1128/aac.00833-06
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Assessment of Entecavir Resistance in Lamivudine-Refractory Hepatitis B Virus Patients Reveals Different Clinical Outcomes Depending on the Resistance Substitutions Present

Abstract: Entecavir (ETV) is a deoxyguanosine analog approved for use for the treatment of chronic infection with wild-type and lamivudine-resistant (LVDr) hepatitis B virus (HBV).In LVD-refractory patients, 1.0 mg ETV suppressed HBV DNA levels to below the level of detection by PCR (<300 copies/ml) in 21% and 34% of patients by Weeks 48 and 96, respectively. Prior studies showed that virologic rebound due to ETV resistance (ETVr) required preexisting LVDr HBV reverse transcriptase substitutions M204V and L180M plus add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
196
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(217 citation statements)
references
References 41 publications
(57 reference statements)
20
196
0
1
Order By: Relevance
“…Several studies have revealed that the 2-year incidence rate of drug-resistance mutations for lamivudine is significantly higher than that of entecavir (18% vs 1%) in immunocompetent patients with chronic HBV infection. 16,17 Our study showed that the 2-year incidences of drug-resistance mutations were 21.0% for lamivudine and 1.0% for entecavir in allo-HSCT recipients, and this is consistent with outcomes seen in immunocompetent patients. These findings imply that the incidence of drug-resistance mutations might not be associated with impaired immune function in allo-HSCT patients.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies have revealed that the 2-year incidence rate of drug-resistance mutations for lamivudine is significantly higher than that of entecavir (18% vs 1%) in immunocompetent patients with chronic HBV infection. 16,17 Our study showed that the 2-year incidences of drug-resistance mutations were 21.0% for lamivudine and 1.0% for entecavir in allo-HSCT recipients, and this is consistent with outcomes seen in immunocompetent patients. These findings imply that the incidence of drug-resistance mutations might not be associated with impaired immune function in allo-HSCT patients.…”
Section: Discussionsupporting
confidence: 73%
“…In this study, there was no evidence of emerging substitutions associated with virologic resistance to entecavir. Extended treatment and observation through 2 years in a similar trial with entecavir in this patient population showed that virologic breakthrough due to entecavir resistance was observed in 9% of patients [29].…”
Section: Discussionmentioning
confidence: 81%
“…However, in LVD-refractory patients, the barrier to resistance is lower because the suppression of HBV replication is not as great and these patients mostly harbor virus with two of the three substitutions required for high-level ETVr [26]. This results in virologic breakthrough with ETVr in LVD-refractory patients at 1% in the first year but increasing to 39.5% after 4 years of therapy [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the first case, the patient received a lower dose of ETV (0.1 mg daily for 52 weeks) than is currently recommended in product labeling. It was shown that LVD-ADV combination therapy was apparently effective for the ETV-resistant strain, presumably because there is no cross-resistance between ETV and ADV [26,27].…”
Section: Discussionmentioning
confidence: 99%